IMAGE QUALITY ASSESSMENT FOR FAKE BIOMETRIC DETECTION: APPLICATION TO IRIS, FINGERPRINT, AND FACE RECOGNITION - Ms. Kavita H. Waghmode; Dr. Prof. P.K. Ajmera (International Journal of Innovations in Engineering Research and Technology, 2021)
In this Paper,the actual presence of a real legitimate trait in contrast to a fake self-manufactured synthetic or reconstructed sample is a significant problem in biometric authentication, which requires the development of new and efficient protection measures. In this paper, we present a novel software-based fake detection method that can be used in multiple biometric systems to detect different types of fraudulent access attempts. The objective of the proposed system is to enhance the security of biometric recognition frameworks, by adding livensassessment in a fast, user-friendly, and non-intrusive manner, through the use of image quality assessment.